Synthesis, thermal behavior in oxidative and pyrolysis conditions, spectroscopic and DFT studies of some alkaline earth metals p-aminobenzoate complexes using TG-DTA, DSC, PXRD and EGA (TG-FTIR) techniques - Teixeira, José Augusto; Fernandes, Richard P.; Isquibola, Guilherme [UNESP]; Gaspari, Ana P. S.; Machado, Antonio E. H.; Caires, Flávio J. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier, 2022)
p-aminobenzoic acid is a substance widely used in several areas, such as catalysis, biomarkers, magnetic materials, luminescent materials and biological applications. p-aminobenzoate complexes with alkaline earth metal were synthesized and the thermal and pyrolysis behavior was studied using thermoanalytical and spectroscopic techniques. Based on TG/DTG-DTA and EGA results, the thermal decomposition mechanisms of the compounds were proposed under both atmospheres studied. The main gaseous products identified by EGA in both study conditions were H2O, Aniline, CO and CO2. From DSC analysis, it was possible to measure the enthalpies of dehydration and evaluate the phase transitions of the magnesium complex. FTIR data suggest that metal-ligand coordination occurs through carboxylate group by different ways. The coordination modes suggested by experimental FTIR data were supported by DFT study. The X-ray diffraction powder patterns show that the barium compound was obtained in amorphous state, while the other compounds have a crystalline structure.
Keywords: Alkaline earth metals; Evolved gases; p-aminobenzoate complexes; Pyrolysis; Thermal behavior; Thermal decomposition mechanism